FENOMENA GERAKAN SEMPALAN UMAT ISLAM INDONESIA (Tinjauan Sosiologi Agama) - Hasbullah Hasbullah (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
Splinter movement is a phenomenon that can be found throughout the ages. More recently, the phenomenon of the emergence of splinter movement or cult was widespread in the country and has caused unrest in society. The presence of splinter movement gave birth also had violence committed by a group of people calling themselves as defenders of Islam. This raises a big question, actually what has happened with the diversity of Indonesian society, so that they form a new flow that is clearly contrary to the teachings of Islam that believes in the ground water. These streams are known in this country called a cult or breakaway flow.